Incorporated TiO2 nanoparticles into PVC/PMMA polymer blend for enhancing the optical and electrical/dielectric properties: Hybrid nanocomposite films for flexible optoelectronic devices - A Al‐Muntaser; Hala M Abo‐Dief; Tarabiah, A E; Alzahrani, Eman; Alsalmah, Hessa A; Alharbi, Zeinab M; Rami Adel Pashameah; Abdu Saeed (Polymer engineering and science, 2023)
In the present work, sol–gel‐synthesized titanium oxide nanoparticles (TiO2 NPs) were added to polyvinyl chloride (PVC) and polymethyl methacrylate (PMMA) to create polymer nanocomposites (PNCs) samples. The preparation was carried out via the solution casting method. The synthesized TiO2 NPs have a tetragonal anatase phase and an average grain size of 15.7 nm. XRD analysis reveals that the TiO2 NPs' addition to PVC/PMMA causes a decrease in the crystallinity of PNCs films. Infrared Fourier analysis demonstrated the interplay/complexity between the PVC/PMMA blend and TiO2 NPs. The UV/visible spectrum of the PVC/PMMA blend showed two absorbance peaks at 278 and 208 nm, which may result from the n → π* and π → π* transitions. Also, optical bandgaps for indirect and direct allowed transitions decreased with increasing TiO2 NPs concentration. The samples' AC electrical conductivity and dielectric properties were measured at room temperature. As the TiO2 NPs content in the nanocomposite rises, a percolating network begins to emerge inside the composite, demonstrating that AC electrical conductivity obeys Jonscher's law. Additionally, it has been demonstrated that nanoparticle concentration leads to a higher composite dielectric loss and dielectric constant. These findings suggest the possibility of using the prepared nanocomposites in capacitive energy storage and optoelectronic devices.HighlightsPVC/PMMA‐TiO2 nanocomposites' films were fabricated via the solution casting method.Adding TiO2 NPs to PVC/PMMA reduces the crystallinity of the PNCs films.The allowed direct and indirect bandgaps decreased with rising TiO2 NPs content.AC conductivity, impedance, and dielectric characteristics were discussed.The findings indicate the use of prepared samples in optoelectronic devices.